From Prussian blue to iron carbides: high-temperature XRD monitoring of thermal transformation under inert gases. (8th May 2017) - Aparicio, Claudia; Filip, Jan; Machala, Libor
Abstract : The thermal behavior and decomposition reaction of Prussian blue (PB) (Fe4 3+ [Fe 2+ (CN)6 ]3 · x H2 O) was studied under inert atmosphere of argon by simultaneous thermogravimetry and differential scanning calorimetry, from room temperature up to 900 °C, with a heating rate of 5 K min −1 . Parallel to the thermogravimetric measurements, the thermal process was monitored by in situ X-ray powder diffraction (XRD) technique under nitrogen atmosphere. The thermogravimetric data show six steps, corresponding to different stages of the decomposition reaction; comparable results are also obtained by in situ XRD. In addition, a set of PB samples heated up to selected temperatures (190, 300, 370, 540, 680, and 790 °C) were ex situ analyzed by powder XRD and Mössbauer spectroscopy. It is found that PB exhibits a negative thermal expansion prior to the water release from its crystalline lattice. Above 300 °C, the decomposition is based on the release of cyanogen gas from the PB structure. At 370 °C, a cubic iron cyanide compound is formed, while at higher temperatures several iron carbides were found. The subsequent thermal treatment of these carbides leads to the formation of metallic iron and graphite.